2013
DOI: 10.1155/2013/621453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylated Vitamin B Complex on Depressive and Anxiety Symptoms and Quality of Life in Adults with Depression

Abstract: Depression, the most common type of mental illness, is the second leading cause of disability and is increasing among Americans. The effect of improved nutrition, particularly with dietary supplements, on depression may provide an alternative to standard medical treatment. Some studies have shown that certain nutrients (e.g., inositol and S-adenosyl methionine) are effective at improving depressed mood, although the results are not unequivocal. The current study was a randomized, double-blind, placebo-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…(combined with vitamin B12 and folate) in patients suffering from depression, 36 perhaps suggesting potential benefits of optimizing B6 status in this patient group. In line with the conclusions of a recent meta-analysis, we observed a positive association of anxiety with hypertension in the current study, the mechanism for which has been previously reviewed but remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(combined with vitamin B12 and folate) in patients suffering from depression, 36 perhaps suggesting potential benefits of optimizing B6 status in this patient group. In line with the conclusions of a recent meta-analysis, we observed a positive association of anxiety with hypertension in the current study, the mechanism for which has been previously reviewed but remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, micronutrients act as cofactors in neurotransmitter synthesis and metabolism, where they can be rate-limiting factors (Ames et al, 2002). There are at least seven randomised controlled trials (RCTs) of B-Complex and combined mineral/vitamin formulations in which improvements in depression, anxiety and stress have been demonstrated (Carroll et al, 2000;Harris et al, 2011;Kennedy et al, 2010;Lewis et al, 2013;Long and Benton, 2013a;Rucklidge et al, 2012;Schlebusch et al, 2000) although not all trials using broadspectrum micronutrients have shown benefit for changing mood and anxiety (Cockle et al, 2000;Haskell et al, 2008Haskell et al, , 2010. However, all the negative trials were conducted on people who had no presenting psychological/psychiatric challenge.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many studies have examined various interventions for the treatment of depression [10][11][12]. Various studies have shown that using different types of physical activity may be useful in treating depression [12][13][14].…”
Section: Introductionmentioning
confidence: 99%